2017
DOI: 10.1111/jade.12139
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a Design Thinker: Assessing the Learning Process of Students in a Secondary Level Design Thinking Course

Abstract: Design thinking is a collaborative problem solving and human‐centric approach that fosters innovation by elevating participants’ creative thinking abilities. Design thinking techniques and practices have been implemented into different curricula in secondary and post‐secondary education to address the need for new skills to be learned for the twenty‐first century. However, little work has been conducted to clarify how to evaluate the students’ design thinking skills gained in these courses. This study reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 13 publications
2
38
1
6
Order By: Relevance
“…Similarly, it is stated in the literature that design thinking contributes to ensuring and facilitating learning (Aflatoony & Wakkary, 2015;Cook & Bush, 2018;Painter, 2018;Vest, 2006), developing the 21st century skills (Anderson, 2012;Canestraro, 2017;Carroll, 2014;Cook & Bush, 2018;Retna, 2016;Rotherham & Willingham, 2009), preparing for the future and the profession (Rotherham & Willingham, 2009). Although these studies in the literature (Aflatoony & Wakkary, 2015;Aflatoony et al, 2018;Anderson, 2012;Canestraro, 2017;Carroll, 2014;Cook & Bush, 2018;Painter, 2018;Retna, 2016;Rotherham & Willingham, 2009;Vest, 2006) support the findings obtained within the scope of the current research in terms of the contributions of design thinking, the current research expands this literature by examining middle school students' views and experiences towards design thinking. For example, the study conducted by Aflatoony et al (2018) on design thinking was carried out to examine the development of design thinking skills (problem solving, collaboration, and being human-centred) in high school students.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 63%
See 1 more Smart Citation
“…Similarly, it is stated in the literature that design thinking contributes to ensuring and facilitating learning (Aflatoony & Wakkary, 2015;Cook & Bush, 2018;Painter, 2018;Vest, 2006), developing the 21st century skills (Anderson, 2012;Canestraro, 2017;Carroll, 2014;Cook & Bush, 2018;Retna, 2016;Rotherham & Willingham, 2009), preparing for the future and the profession (Rotherham & Willingham, 2009). Although these studies in the literature (Aflatoony & Wakkary, 2015;Aflatoony et al, 2018;Anderson, 2012;Canestraro, 2017;Carroll, 2014;Cook & Bush, 2018;Painter, 2018;Retna, 2016;Rotherham & Willingham, 2009;Vest, 2006) support the findings obtained within the scope of the current research in terms of the contributions of design thinking, the current research expands this literature by examining middle school students' views and experiences towards design thinking. For example, the study conducted by Aflatoony et al (2018) on design thinking was carried out to examine the development of design thinking skills (problem solving, collaboration, and being human-centred) in high school students.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 63%
“…However, since the implementation of design thinking in education has only been given importance in recent years (Lor, 2017), there are very few studies on the implementation of design thinking in education (Razzouk & Shute, 2012). It is observed that studies on the subject generally focus on the effect of design thinking on the 21st century skills such as creativity and innovation, communication and cooperation (Aflatoony, Wakkary & Neustaedter, 2018;Anderson, 2012;Carroll, Goldman, Britos, Koh, Royalty ve Hornstein, 2010), and teachers' perceptions, views and experiences towards the application of design thinking (Aflatoony & Wakkary, 2015;Painter, 2018;Retna, 2016). However, in the literature on the subject, no research examining the views and experiences of middle school students towards the design thinking approach has been found.…”
Section: Introductionmentioning
confidence: 99%
“…as it encourages creativity and innovation with an empathic, flexible, and iterative approach (Henriksen, Richardson & Metha, 2017;Lor, 2016). It is known that DT is used as a method, process, and skillset in the field of education together with the search of a teaching strategy suitable for 21 st century skills, work habits, and character traits (Aflatoony & Wakkary, 2018;Carroll, 2014;Dukes & Koch, 2012). In creative programming activities, DT is used as a human-centered teaching method.…”
Section: Design Thinking (Dt)mentioning
confidence: 99%
“…In the work of Duman and Kayali (2017), it is observed that teaching activities concentrating on the design thinking process were effective in the development of secondary school students' design thinking skills. The bottom line reached by Aflatoony et al (2018) shows that high school students develop their design thinking skills to a certain extent through the design thinking program established. The outcomes of this study coincide with the data obtained by Duman and Kayali (2017) and Aflatoony et al (2018).…”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation